Neuroendoscopic surgery for unilateral hydrocephalus due to inflammatory obstruction of the Monro foramen - Francisco A. Vaz-Guimarães Filho; Clauder O. Ramalho; Ítalo C. Suriano; Samuel T. Zymberg; Sérgio Cavalheiro (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Unilateral hydrocephalus (UH) is characterized by enlargement of just one lateral ventricle. In this paper, the authors will demonstrate their experiences in the neuroendoscopic management of this uncommon type of hydrocephalus. METHOD: The authors retrospectively reviewed a serie of almost 800 neuroendoscopic procedures performed from September 1995 to July 2010 and selected seven adult patients with UH. Clinical and radiological charts were reviewed and analyzed. RESULTS: Six patients had intraventricular neurocysticercosis and one patient had congenital stenosis of the foramen of Monro. Headaches were the most common symptom. A septostomy restored cerebrospinal fluid circulation. During follow-up period (65.5 months, range 3-109) no patient has presented clinical recurrence as well as no severe complications have been observed. CONCLUSION: UH is a rare condition. A successful treatment can be accomplished through a neuroendoscopic approach avoiding the use of ventricular shunts.